Disease-modifying targets in neurodegenerative disorders : paving the way for disease-modifying therapies - Baekelandt, Veerle; Lobbestael, Evy (Academic Press, 2017)
Disease-Modifying Targets in Neurodegenerative Disorders: Paving the Way for Disease-Modifying Therapies examines specific neurodegenerative disorders in comprehensive chapters written by experts in the respective fields. Each chapter contains a summary of the disease management field, subsequently elaborating on the molecular mechanisms and promising new targets for disease-modifying therapies. This overview is ideal for neuroscientists, biomedical researchers, medical doctors, and caregivers, not only providing readers with a summary of the way patients are treated today, but also offering a glance at the future of neurodegenerative disorder treatment. This book provides a comprehensive overview of how key proteins in neurodegenerative disorders can be used as targets to modify disease progress and summarizes how patients are treated today, providing a glance at future disease management. This book includes intelligible and informative information that is perfect for non-specialists, medical practitioners, and scientists.